Geochemical Characterization and Economic Potential of Emure and Ijero Ekiti Pegmatites in Southwest Nigeria (Nigerian Journal of Technology, 2021)
Global demand increase for rare metals deposits has re-enacted the search for economically viable deposits. Pre-cambrian pegmatites occurring as near dykes and massive types were studied for Emure-Ekiti and Ijero-Ekiti respectively, with the aim of characterizing them geochemically and determining their possible economics values. A total of twelve samples comprising seven from Emure-Ekiti, three whole rock muscovite extract for Ijero-Ekiti were analysed for major and trace elements using X-ray fluorescence method. Thin sections prepared for the Emure-Ekiti pegmatites show that quartz, microcline are major mineral constituents. The geochemical results reveals that the Emure-Ekiti and the whole rock samples of Ijero-Ekiti are considerably siliceous, with an average value of 68.72% and 68.6% respectively, while the muscovites extracts average 48.86%. Mean values of major oxides for the Emure, Ijero[whole rock, muscovite] are as follows; Al2O3 -20.42%,[13.74%, 35.15%]; Fe2O3 - 1.83%,[1.24%, 2.19%]; MgO- 0.013%,[0.029%, 1.04%]; CaO - 0.02%,[0.34%, 2.4%]; Na2O – 1.01%,[4.40%, 1.045%]; K2O – 3.17%,[2.77%, 11.07%]. Trace and rare-earth elements result shows that the Emure-Ekiti pegmatites is “barren” – depleted in rare metals Ta, Nb, Cs, Sn, Rb e.t.c and compare favourably with Apomu ,Ago-Iwoye and Ijebu-Ife barren pematites. On the other hand, two of the whole rock samples are mineralized- fairly enriched in rare metals Ta, Nb, Rb while the remaining sample and the muscovite extract are barren; as depicted by the Rb Vs Rb plot and when compared to the other rare metal pegmatites across the world.